Current issues and future directions in gymnastics research: biomechanics, motor control and coaching interface. Issue 2 (1st February 2023) - Farana, R.; Williams, G.; Fujihara, T.; Wyatt, H. E.; Naundorf, F.; Irwin, G.
ABSTRACT: The sport of gymnastics is undergoing a global examination of its culture and the relationship between the gymnast, coach and environment is a central focus. The aim of this review is to explore biomechanics and motor control research in skill development and technique selection in artistic gymnastics with a focus on the underlying concepts and scientific principles that allow performance enhancement, skill development and injury risk reduction. The current review examines peer reviewed papers from 2000 onwards, with a focus on contemporary approaches in the field of gymnastics research, and highlights several key directions for future gymnastics research. Based on our review and the integration of the models of Newell (1986) and Irwin et al. (2005), we recommend that future gymnastics research should embrace at the very least a multidisciplinary approach and aim for an interdisciplinary paradigm.